DAMPAK ADVERTISING DAN PEMBENTUKAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECAP ABC PADA PT.HEINZ ABC INDONESIA DI SAMARINDA - Juriyanto Eka Yudhyani (Prodi Ilmu Administrasi Negara, 2015)
ABC ketchup is ketchup first time in Indonesia produced by ABC PT.Heinz Indonesia.Destination this study to determine the effect of advertising and brand awareness on product purchasing decisions on PT.Heinz ABC soy sauce in Samarinda Indonesia and to know between advertising and brand awareness, which is more variable influence on the purchasing decisions of soy sauce PT.Heinz ABC in Indonesia in Samarinda.A primary issue in the writing of this study is whether advertising and brand awareness significantly influence purchasing decisions on PT.Heinz ABC soy sauce in Indonesia samarinda.Basic theory used marketing management, advertising, brand awareness and decision purchase.Hypothesis: advertising and brand awareness significantly influence purchasing decisions on PT.Heinz ABC soy sauce in Indonesia and advertising samarinda dominant influence on purchasing decisions on PT.Heinz ABC soy sauce Indonesia in samarinda.The analytical tool used ismultiplelinearregression.These results gain coefficient of determination (R2) of the regression equation of 0.773 or 77.3% which shows that advertising and brand awareness simultaneously accounted for 77.3% of the purchase decision (Y) ABC soy sauce in the village river siring northern districts samarinda samarinda city.The simultaneous influence of proving that the influence of these two variables proved and of the two variables are the most influential advertising variable (X1). From the results of these studies should further improve Ketchup ABC advertising program with the program more attractive and more appropriate use of the media to increase brand awareness so that consumers' purchasing decisions Ketchup ABC increasing. In addition, Ketchup Company ABC should consider other means of promotion in addition to advertising in order of performance and corporate objectives can be achieved with more good. technique this study support the hypothesis.